Rasionalitas Mahasiswa Menikah pada Masa Tugas Akhir di Kota Tanjungpinang - Atika Rokhim; Siti Arieta; Sri Wahyuni (Pusat Riset dan Inovasi Nasional, 2023)
Describes the rational choices made by Tanjungpinang City students in deciding to get married. And this research discusses the factors for students in their decision to get married, the impact felt and the problems faced when deciding to get married. This research uses a qualitative type of research method with a phenomenological approach. The data sources in this study were obtained using data collection techniques through interviews and documentation. The subjects of this study were students who decided to get marriedduring their final year. The results of this study are in the form of an analysis of the factors or background of each informants is based on several factors, namely external factors such as family, economy, environment and religion. And there are also internal factors such as desire and opportunity. There is alsi an impact felt bystudents on their decision to get married, namely the impact on social life, where problems arise that can affect the field of education being undertaken and the strategies used by students in dealing with obstacles in the process of completing their studies. The theory used in this research is the rational choice developed by James S Coleman. So that it can be seen that the decisions taken by students in their decision to get married are (1) there is motivation that grows from the social environment to get married young, (2) religion that influencces student decisions to get married, (3) the decision to get married because they get advice from their parents, (4) mutual love.